Cena enunciativa salão de beleza/estética: constituição do ethos discursive - Souza, Danilo Araujo de [UNIFESP] (2016)
This paper proposes the analysis of the discourse produced by speakers belonging to the same enunciative scene, in this case, a beauty/aesthetics salon. The theoretical basis is based mainly on French Discourse Analysis from the perspective of Dominique Maingueneau. Engendered in this theoretical pillar, the research is directed to three concepts that become fundamental: the discursive ethos, the enunciative scene and the argumentation. The research has a qualitative approach of exploratory character, in which the data collection is done atTássio?sCabeleireiros, considering the interviewees of different genders, ages, professional functions and schooling. We start from the following research question: How the discursive ethos constituted as anargumentative mechanismin the discourse of beauty/aesthetics professionals, considering the interference of the workplace and the power relations as hierarchies and minority discourses?The research objectives were to analyze the constitution of the subjects? discursive ethos, considering the interference of the enunciative scene and, consequently, of the scenographies, as well as evidencing the view of themselves of the subjects. The relevance of this study is mainly due to its novelty, since none scientific work with the theme of this research was glimpsed, besides, of course, the yearning for explanations about discursive phenomena evidenced in an environment as diverse as the beauty/aesthetics salon, holder of several enunciative scenes. The initial hypothesis was that the constitution of the discursive ethos of research subjects would be an element of argumentation, especially considering topics such as the taste for the profession, the prejudice and belonging (or not) to the social group of beauty/aesthetics professionals, considering, primarily, the scenography in which each subject produces the enunciation. The analysis of the corpus (with 04 subjects) of this research confirm the hypothesis and answer the research question, since it was verified how the discursive ethos of these subjects is built as an argumentative element, also considering the Speech Act Theory, by Austin (1990). It was also observed that the enunciative scene has interference from the workplace and the inter and intrapersonal relations that are established, characterizing relations of power, marked by the hierarchies within that environment.